Accuracy of central neuro-imaging review of DIPG compared with histopathology in the International DIPG Registry. Issue 5 (20th October 2021) - Lazow, Margot A; Fuller, Christine; DeWire, Mariko; Lane, Adam; Bandopadhayay, Pratiti; Bartels, Ute; Bouffet, Eric; Cheng, Sylvia; Cohen, Kenneth J; Cooney, Tabitha M; Coven, Scott L; Dholaria, Hetal; et al.
Abstract: Background: Diffuse intrinsic pontine glioma (DIPG) remains a clinico-radiologic diagnosis without routine tissue acquisition. Reliable imaging distinction between DIPG and other pontine tumors with potentially more favorable prognoses and treatment considerations is essential. Methods: Cases submitted to the International DIPG registry (IDIPGR) with histopathologic and/or radiologic data were analyzed. Central imaging review was performed on diagnostic brain MRIs (if available) by two neuro-radiologists. Imaging features suggestive of alternative diagnoses included nonpontine origin, <50% pontine involvement, focally exophytic morphology, sharply defined margins, and/or marked diffusion restriction throughout. Results: Among 286 patients with pathology from biopsy and/or autopsy, 23 (8%) had histologic diagnoses inconsistent with DIPG, most commonly nondiffuse low-grade gliomas and embryonal tumors. Among 569 patients with centrally-reviewed diagnostic MRIs, 40 (7%) were classified as non-DIPG, alternative diagnosis suspected. The combined analysis included 151 patients with both histopathology and centrally-reviewed MRI. Of 77 patients with imaging classified as characteristic of DIPG, 76 (99%) had histopathologic diagnoses consistent with DIPG (infiltrating grade II-IV gliomas). Of 57 patients classified as likely DIPG with some unusual imaging features, 55 (96%) had histopathologic diagnoses consistent with DIPG. Of 17 patients with imaging features suggestive of an alternative diagnosis, eight (47%) had histopathologic diagnoses inconsistent with DIPG (remaining patients were excluded due to nonpontine tumor origin). Association between central neuro-imaging review impression and histopathology was significant ( p < 0.001), and central neuro-imaging impression was prognostic of overall survival. Conclusions: The accuracy and important role of central neuro-imaging review in confirming the diagnosis of DIPG is demonstrated.